Strategies to target the cancer driver MYC in tumor cells - Weber, Leonie I.; Hartl, Markus (Frontiers in Oncology, 2023)
The MYC oncoprotein functions as a master regulator of cellular transcription and furthermore executes non-transcriptional tasks relevant for DNA replication and cell cycle regulation, thereby interacting with multiple proteins. MYC is required for fundamental cellular processes triggering proliferation, growth, differentiation, or apoptosis, but also represents a major cancer driver being aberrantly activated in most human tumors. Due to its non-enzymatic biochemical functions and largely unstructured surface MYC has remained difficult to be directly addressed by specific inhibitor compounds, and consequently alternative approaches leading to indirect MYC inhibition have been evolved. Nowadays, multiple organic compounds, nucleic acids, or peptides specifically interfering with MYC activities are in preclinical or early stage clinical studies but none of them has been approved so far for pharmacological treatment of cancer patients. In addition, specific and efficient delivery technologies to deliver MYC-inhibiting agents into MYC-dependent tumor cells are just beginning to emerge. In this review, a brief overview of direct and indirect MYC-inhibiting agents and their individual modes of MYC inhibition is given. Furthermore, we summarize current possibilities to deliver appropriate drugs into cancer cells containing derailed MYC using viral vectors or appropriate nanoparticles. Finding the right formulation to target MYC-dependent cancers and to achieve a high intracellular concentration of compounds blocking or attenuating oncogenic MYC activities could be as important as the development of novel MYC-inhibiting principles.